2005
DOI: 10.1593/neo.05178
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprofiles of 11 Biomarkers Using Tissue Microarrays Identify Prognostic Subgroups in Colorectal Cancer

Abstract: Our study highlights the potential of TMAs for a higher-dimensional analysis by evaluating serial sections of the same tissue core (three-dimensional TMA analysis). In addition, it endorses the use of immunohistochemistry supplemented by hierarchical clustering for the identification of tumor subgroups with diagnostic and prognostic signatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 32 publications
2
59
0
1
Order By: Relevance
“…The "overexpression" of ADAM10 in MCL tumors per se may be biologically important, because one previous report showed that overexpression of ADAM10 in colorectal cancer was significantly correlated with a higher clinical stage. 16 In this study, we demonstrated that 5 of 5 cases of MCL showing ADAM10 immunoreactivity also expressed the active/mature form of ADAM10. It is likely that most MCL tumors overexpress ADAM10 and carry constitutive activation of this protein.…”
Section: Adam10 Inhibition Enhanced the Growth-suppressing Effect Of supporting
confidence: 49%
See 1 more Smart Citation
“…The "overexpression" of ADAM10 in MCL tumors per se may be biologically important, because one previous report showed that overexpression of ADAM10 in colorectal cancer was significantly correlated with a higher clinical stage. 16 In this study, we demonstrated that 5 of 5 cases of MCL showing ADAM10 immunoreactivity also expressed the active/mature form of ADAM10. It is likely that most MCL tumors overexpress ADAM10 and carry constitutive activation of this protein.…”
Section: Adam10 Inhibition Enhanced the Growth-suppressing Effect Of supporting
confidence: 49%
“…15 In another study, ADAM10 expression detectable by immunohistochemistry in colorectal cancer patient samples was found to be correlated with a higher clinical stage. 16 Using immunohistochemistry, it was also found that ADAM10 is overexpressed in squamous cell carcinomas of the oral cavity compared with the benign epithelial cells; knockdown of ADAM10 expression using short interfering RNA (siRNA) in the cell lines derived from these tumors was shown to induce a significant decrease in cell growth. 17 Similar findings were made in pancreatic cancer, in which inhibition of ADAM10 expression in pancreatic carcinoma cell lines resulted in a significant decrease in invasiveness and migration.…”
Section: Introductionmentioning
confidence: 99%
“…The clustering outcomes made biological sense when compared with groups of eyes with morphologically recognizable stages of glaucoma. Clustering analyses have proven useful for identifying gene expression differences that distinguish various known types and stages of cancer (28,29). To our knowledge, clustering analysis has not been previously used to distinguish and order early states of a complex multifactorial disease (or any other disease) in samples that are morphologically similar to unaffected controls.…”
Section: Figurementioning
confidence: 99%
“…Clustering genes in microarray datasets according to their expression profiles is a powerful approach that has identified molecular signatures that predict cancer progression (28,29). Clustering methods group the most similar samples based on the expression profiles of many relevant genes.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical clustering is an unbiased computational method for grouping samples based on the similarity of their gene expression profiles. It is a powerful approach for characterizing stages of cancer and other diseases (26)(27)(28). Here, we used hierarchical clustering to analyze our gene expression data.…”
Section: Bone Marrow Transfer Is Not Required For Protectionmentioning
confidence: 99%